ZKSCAN1 gene and its related circular RNA (circZKSCAN1) both inhibit hepatocellular carcinoma cell growth, migration, and invasion but through different signaling pathways. Issue 4 (17th March 2017) - Yao, Zhicheng; Luo, Jingyan; Hu, Kunpeng; Lin, Jizong; Huang, He; Wang, Qiangliang; Zhang, Peng; Xiong, Zhiyong; He, Chonghua; Huang, Zejian; Liu, Bo; Yang, Yang
Abstract : There is increasing evidence that circular RNA (circRNA) are involved in cancer development, but the regulation and function of human circRNA remain largely unknown. In this study, we demonstrated that ZKSCAN1, a zinc finger family gene, is expressed in both linear and circular ( circZKSCAN1 ) forms of RNA in human hepatocellular carcinoma (HCC) tissues and cell lines. Here, we analyzed a cohort of 102 patients and found that expression of both ZKSCAN1 mRNA and circZKSCAN1 was significantly lower ( P  < 0.05) in the HCC samples compared with that in matched adjacent nontumorous tissues by reverse transcription PCR (RT‐PCR). The low expression level of ZKSCAN1 was only associated with tumor size ( P  =   0.032), while the cirZKSCAN1 levels varied in patients with different tumor numbers ( P  <   0.01), cirrhosis ( P  =   0.031), vascular invasion ( P  =   0.002), or microscopic vascular invasion ( P  =   0.002), as well as with the tumor grade ( P  <   0.001). Silencing both ZKSCAN1 mRNA and circZKSCAN1 promoted cell proliferation, migration, and invasion. In contrast, overexpression of both forms of RNA repressed HCC progression in vivo and in vitro . Silencing or overexpression of both forms of RNA did not interfere with each other. RNA‐seq revealed a very different molecular basis for the observed effects; ZKSCAN1 mRNA mainly regulated cellular metabolism, while circZKSCAN1 mediated several cancer‐related signaling pathways, suggesting a nonredundant role for ZKSCAN1 mRNA and circRNA. In conclusion, our results revealed two post‐translational products ( ZKSCAN1 mRNA and circZKSCAN1 ) that cooperated closely with one another to inhibit growth, migration, and invasion of HCC. cirZKSCAN1 might be a useful marker for the diagnosis of HCC. Abstract : Circular RNA have recently been shown to play a regulatory role in disease. We investigated the role of circRNA transcribed from ZKSCAN1, a member of the zinc finger family. Our results revealed two post‐translational products ( ZKSCAN1 mRNA and circZKSCAN1 ) that cooperated closely with one another to inhibit cancer growth migration and invasion, but which affected different signaling pathways.